Complicação da banda gástrica ajustável videolaparoscópica para tratamento da obesidade mórbida: extrusão da banda - Zuccaro,Ana Maria (2003)
Various options for surgical treatment of morbid obesity have been developed with varying results: vertical banded gastroplasty with intestinal by-pass, disabsorptive surgeries and laparoscopic adjustable gastric banding. Although all of them have been effective in weight loss, lower rates of early and late postoperative complications have been described in some procedures. Laparoscopic adjustable silicone gastric banding (LASGB) has a similar principle as vertical banded gastroplasty and it is a minimally invasive procedure, with low systemic and operative problems, but not free of them. We report two rare cases of this complications of LASGB.